Winter wheat productivity depending on weather conditions during early spring period in the Northern Steppe of Ukraine - Мостіпан, М. І.; Умрихін, Н. Л. (Scientific Progress & Innovations, 2018)
It has been established that in the Northern Steppe of Ukraine the beginning of spring vegetation of winter wheat starts at different periods of time. The earliest vegetation (February 22) was observed in 1990, and the latest vegetation (April 4) was in 2003. Therefore, it has been suggested to distinguish the very early (the third decade of February) beginning of vegetation, early beginning of vegetation (the first–second decade of March), middle-time vegetation (the third decade of March) and late beginning of vegetation (the first decade of April) of winter wheat. During the whole period of observations from 1986 to 2005, the very early beginning of vegetation was observed during 3 years (15%), early vegetation – 4 years (20%), middle-time vegetation – 8 years (40%), and late vegetation – 5 years (25%). The analysis of winter wheat productivity shows that the later is the beginning of spring vegetation, the less productivity of winter wheat. During the very early spring vegetation in the third decade of February, productivity is twice as large as compared with the late vegetation in the first decade of April. On average, over the years of the study, these indicators were 6.74 and 3.28 t/ha respectively. In the very early vegetation (the 3rd decade of February), productivity of the mixed-age crops is almost the same and ranges from 6.44 to 6.96 t/ha. During the late vegetation (early April), the highest productivity is formed by the crops sown from the 10th to the 25th of September. Their average productivity during the years of the study was 3.86–3.91 t/ha. With this period of spring vegetation, the productivity of crops sown on September 2nd and October 2nd is almost the same and is 2.99 and 2.88 t/ha respectively, but significantly higher than the productivity of crops sown on August 25th. For the formation of winter wheat harvest, the change of the average daily temperature above 0 °C is important, as well as the duration of the period from that time to the beginning of spring vegetation. That is the steady increase in average daily air temperature to more than +5 °С. The increase in the period of time from the date of the change of the average daily air temperature above 0 °C to the beginning of spring vegetation causes the decrease in the productivity of winter wheat. During the years when the duration of this period was up to 10 days, the productivity of winter wheat averaged 6.04 t/ha, and during the years with this period of more than 30 days, the productivity decreased to 3.76 t/ha. The shorter period from the change of the average daily air temperature above 0 °C to the time of the beginning of spring vegetation, the higher the dependence of the level of winter wheat productivity on the sowing terms. If this period is longer than 30 days, the highest productivity was formed by crops sown on September 17th and September 25th, and during the years when this period lasted from 10 to 20 days, higher productivity was provided by the crops sown from September 10th to September 25th. With the duration of the period from the date of the change of the average daily air temperature above 0 °C to the beginning of spring vegetation to 20 days, the productivity of winter wheat crops with early sowing on September 2nd and October 2nd is almost the same. The crops sown on September 2nd with the duration of this period up to 10 days formed productivity of 5.44 t/ha, and the crops sown on October 2nd – 5.56 t/ha. At the same time, if the duration of this period exceeds 20 days, the crops sown on October 2nd form a considerably higher productivity than the crops sown on September 2nd.